Interfacial agent effect on rheological response and crystallite characteristics in germicidal polypropylene/titanium dioxide nanocomposites - Serrano, Cristina (2012)
Germicidal nanocomposites based on metallocene isotactic polypropylene (iPP) and titanium dioxide (TiO 2) nanoparticles have been prepared at a constant TiO 2 content of 2 wt%. Different quantities of a polypropylene wax partially grafted with maleic anhydride (PP-g-MAH) are employed to improve the polymer-nanoparticle compatibility. Remarkable biocidal capabilities of these TiO 2 nanocomposites have been found and their crystalline structure and thermal and rheological responses explored. Several very interesting features have been found in these germicidal nanocomposites. On the one hand, rheological parameters do not change significantly with respect to those exhibited by pure iPP. This is extremely advantageous for the processing of these compounds since they can be transformed under similar conditions to those employed for iPP. On the other hand, the existence of two polymorphs is observed independent of the amount of compatibilizer used. The enhancement in polymer-nanoparticle interactions by effect of the interfacial (PP-g-MAH) component is appraised looking at dynamical mechanical relaxations as a function of temperature and at crystallization processes of the various nanocomposites.